The efficacy of unsupervised home-based exercise regimens in comparison to supervised lab-based exercise training upon cardio-respiratory health facets - Blackwell, J.; Atherton, Philip J.; Smith, Kenneth; Doleman, Brett; Williams, John P.; Lund, Jonathan N.; Phillips, Bethan E. (Wiley Open Access, 2017)
Supervised high-intensity interval training (HIIT) can rapidly improve cardiorespiratory fitness (CRF). However, the effectiveness of time-efficient unsupervised home-based interventions is unknown. Eighteen volunteers completed either: laboratory-HIIT (L HIIT); home-HIIT (H-HIIT) or home-isometric hand-grip training (H-IHGT). CRF improved significantly in L-HIIT and H-HIIT groups, with blood pressure improvements in the H-IHGT group only. H-HIIT offers a practical, time-efficient exercise mode to improve CRF, away from the laboratory environment. H-IHGT potentially provides a viable alternative to modify blood pressure in those unable to participate in whole-body exercise.